The Relationship of Stress to the Number of Assignments and the Health Impact of UINSU Students - Wati, Desi Indriani Rahma (Jurnal Pengabdian Nusantara, 2024)
The number of assignments to students has become commonplace when someone undergoes lectures in college. The number of tasks has a slight influence on the health of students, especially UINSU students who need time and energy. Whether UINSU students care about health is a question. In addition to carrying out tasks properly and on time, as students we need to maintain health. According to the World Health Organization (WHO), health is a state of complete physical, mental, and social well-being and not simply the absence of disease or infirmity. Health is not only physical or visible from the outside, but mental health is also an important aspect of health. Coupled with current conditions that make learning activities the cause of many students' current coursework and reduce the intensity of student social interaction. This paper aims to determine the effect of many tasks on the health of UINSU students. The research method used is a descriptive research method by taking data through questionnaires and direct interviews. From the data we have obtained from the results of the study, it can be concluded that the average percentage of sleep time of UINSU students before and after entering college has decreased and many students feel their eating and sleeping patterns are disturbed due to the large number of coursework.